Shorter Inter-donation interval contributes to lower cell counts in subsequent stem cell donations - Panch, Sandhya R. (Transplant Cell Ther, 2021)
BACKGROUND: Approximately 7% of unrelated hematopoietic stem cell donors are asked to donate stem cells a subsequent time to the same or different recipient. Recent studies have shown that donation related symptoms for second donations were similar to the first donation experiences. Little is known about differences in stem cell mobilization and yields for subsequent peripheral blood stem cell (PBSC) and bone marrow (BM) collections. OBJECTIVES: We hypothesized that CD34+ cell yields and total nucleated cell (TNC) concentrations for subsequent PBSC or BM donations are lower than those at the first donation. We also evaluated the factors influencing stem cell yields in healthy unrelated second time donors. STUDY DESIGN: Data were gathered from the Center for International Blood and Marrow Transplant Research (CIBMTR) database on 513 PBSC and 43 BM donors who donated a second. Time between 2006 and 2017 through the National Marrow Donor Program (NMDP). RESULTS: Among second time PBSC donors, we found significantly lower pre-apheresis peripheral blood CD34+ cells counts (10(6)/L) (68.6 vs. 73.9; p=0.03), and collection yields (x10(6)) (556 vs. 608; p=0.02) at the second donation compared to the first. This decrease at the subsequent donation was associated with a shorter inter-donation interval, decrease in BMI, and a lower total G-CSF dose. In most instances, sub-optimal mobilizers at first donation donated suboptimal numbers of HSC at their subsequent donations. Among repeat BM donors, the TNC concentration was lower at the second donation. A low sample size in this group precluded additional analysis. CONCLUSIONS: Overall, when considering repeat donations, increasing inter-donation intervals and evaluating for BMI changes should be considered to optimize stem cell yields. Some of these parameters may be improved by increasing G-CSF dose in PBSC donors within permissible limits.